2016
DOI: 10.1002/pat.3993
|View full text |Cite
|
Sign up to set email alerts
|

Improving the water resistance of epoxy-anhydride matrices by the incorporation of bentonite

Abstract: Epoxy–anhydride‐based polymers are commonly used as a matrix in pipeline systems exposed to water during their in‐service life. Water absorption at moderate temperatures and/or at long exposure times could lead to irreversible hydrolysis reaction decreasing considerably the polymer overall performance. A strategy to enhance the barrier properties of epoxy resins is to add nanofillers to traditional matrices. In this work, we added bentonite and chemically modified bentonite to this purpose. Water absorption of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
6
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 37 publications
2
6
1
Order By: Relevance
“…The aging temperature mainly affected the diffusivity of filled epoxy, where the increase of aging temperature increased the diffusivity, as reported by Liu et al [7] on the clay-filled epoxy. However, Capiel et al [13] reported that increasing aging temperature increased both the maximum water uptake and diffusivity on the bentonite-filled epoxy. The increase in water uptake occurred due to the epoxy-anhydride hydrolysis degradation.…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…The aging temperature mainly affected the diffusivity of filled epoxy, where the increase of aging temperature increased the diffusivity, as reported by Liu et al [7] on the clay-filled epoxy. However, Capiel et al [13] reported that increasing aging temperature increased both the maximum water uptake and diffusivity on the bentonite-filled epoxy. The increase in water uptake occurred due to the epoxy-anhydride hydrolysis degradation.…”
Section: Introductionmentioning
confidence: 98%
“…The insignificant effect of MWCNT on the equilibrium water uptake was likely caused by the increase of bonded water due to opening polar groups after introducing MWCNT. Meanwhile, Capiel et al [13] reported the rise of water uptake with the increase of bentonite content aged at temperature of 22°C, which was also caused by increasing the polar groups. The aging temperature mainly affected the diffusivity of filled epoxy, where the increase of aging temperature increased the diffusivity, as reported by Liu et al [7] on the clay-filled epoxy.…”
Section: Introductionmentioning
confidence: 99%
“…The ANN model allows identifying critical points like the precise temperature at which a particular system's water uptake goes beyond a predefined threshold, work [1], the nano-scale morphology obtained in TBHP-bentonite composites decreases the concentration of water molecules in contact with network backbone, which was confirmed by a smoother Tg versus mass uptake decrease reported in previous publications [1]. The decrease in water-reactive site concentration, produces a reduction on the hydrolysis rate, and extends the service life.…”
Section: Resultsmentioning
confidence: 99%
“…Many authors have found a considerably improvement in barrier properties of epoxy systems containing small amounts of clay as reinforcement [11]- [18]. The effect on water absorption behavior of adding bentonite and chemically modified bentonite to an epoxyanhydride system was studied in a previous work [1]. It was found that epoxyanhydride systems containing small amounts of chemically modified bentonite show higher water resistance than bentonite-epoxy composites and neat matrix.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation